EFFECT OF BIOFERTILIZERS ON SOYBEAN GROWTH AND THEIR KEY PEST DENSITIES AS ALTERNATIVE APPROACH TOWARD SUSTAINABLE AGRICULTURE PRODUCTION - Alaa R. Fadel; Feryal H. Sadiq; Hassan M. Lilo (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Soybean (Glycine max L.) is one of the most important crops belong to the leguminous family native to East Asia. Chemical fertilizers are widely used to increase production in quantity and quality. As a result of the harmful effects caused by chemical fertilizers, it become necessary to find alternative solutions as sustainable approach toward supply plant by elements needs such as biofertilizers. In this study, Bradyrhizobium japonicum alone or in combination of microorganism inoculation included (B. japonicum, Bacillus subtilis, Glomus mosseae, and Anabaena azollae) were tested toward soybean growth parameters under open field condition. Results showed that there is a significant differences in terms of plant height, vegetative and dry grain of soybean and other parameters with combined inoculation and B. japonicum alone in compare with control treatments. Moreover, key pest larval density were also affected by treatments such as Popillia japonica, Spodoptera littoralis and Agrotis ipsilon. The results suggest the use of specific combination of microorganism is recommended as alternative approaches toward sustainable agriculture production of soybean crop.